УЛС ТӨРИЙН МАНИПУЛЯЦИ БА ОЛОН НИЙТИЙН ДИПЛОМАТ АЖИЛЛАГАА - Д.Долгорсүрэн (Politology, 2023)
This article refers to the difference between political manipulation and public diplomacy. The political manipulation is the major problem of research of sociopolitical sciences which is still insufficiently studied in the scientific literature. Naturally, in one article it is impossible to capture all aspects of both political manipulation and public diplomacy: therefore I would like to consider their concepts and definitions by comparing them with one another.